2016
DOI: 10.1037/spq0000136
|View full text |Cite
|
Sign up to set email alerts
|

Latino immigration: Preparing school psychologists to meet students’ needs.

Abstract: As the population of immigrant Latino students continues to rise, school psychologists serving Latino children and families must develop the knowledge and skills necessary to provide high-quality psychological services to culturally and linguistically diverse students from immigrant families. Following a review of the relevant literature on the educational, social, and emotional needs of immigrant Latino children, we describe Project SUPERB (Scholars Using Psychology and Education to Reach Bilinguals), a grant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, after direct experience working with Latino students, teachers are able to have a more individualized view of students apart from population statistics they may have learned in a teacher preparation program. This is not to minimize challenges facing Latino populations in the United States that interfere with school success (Benner & Graham, 2011;Garcia-Joslin et al, 2016), but to point out that present study findings suggest that more experienced teachers are able to see past generalized risk factors to view students as well-behaved and capable individuals, regardless of race/ethnicity. In addition, previous research has found that, although new teachers may enter the field feeling well prepared (knowledge-wise), knowledge does not immediately translate to effective teaching practices (Ronfeldt, Matsko, Nolan, & Reininger, 2018).…”
Section: Teaching Experience Perceptions Of Student Outcomes and Ramentioning
confidence: 70%
“…However, after direct experience working with Latino students, teachers are able to have a more individualized view of students apart from population statistics they may have learned in a teacher preparation program. This is not to minimize challenges facing Latino populations in the United States that interfere with school success (Benner & Graham, 2011;Garcia-Joslin et al, 2016), but to point out that present study findings suggest that more experienced teachers are able to see past generalized risk factors to view students as well-behaved and capable individuals, regardless of race/ethnicity. In addition, previous research has found that, although new teachers may enter the field feeling well prepared (knowledge-wise), knowledge does not immediately translate to effective teaching practices (Ronfeldt, Matsko, Nolan, & Reininger, 2018).…”
Section: Teaching Experience Perceptions Of Student Outcomes and Ramentioning
confidence: 70%
“…In contrast, in quantitative research it was referred to as a risk or resource with the same frequency (N = 15). Low educational level and family income were found to hamper parents' efforts to effectively support their children's learning Montazer & Wheaton, 2011;Moon et al, 2009;Sadownik & Mikiewicz, 2016) and were associated with higher vulnerability of children (Cook et al, 2015;Garcia-Joslin et al, 2016;Lin et al, 2011;Moinolnolki & Han, 2017;Murat & Frederic, 2015;, whereas higher levels of parental social capital were associated with fewer child difficulties at school (Moinolmolki, 2019;Montazer & Wheaton, 2011;Shoshani et al, 2016;Valdez et al, 2013). On the other hand, a few articles (e.g.…”
Section: Parental Backgroundmentioning
confidence: 99%
“…For example, in Texas, a state with a relatively high percentage of English language learners (ELLs), there have been shortages of both special educators and bilingual teachers in every year since 1990. What information is available indicates a shortage of Spanish-speaking special educators, school psychologists (Garcia-Joslin et al, 2016), health service psychologists (American Psychological Association, 2016), and primary care physicians (Zuckerman et al, 2013) relative to the numbers of Spanish speakers in their communities.…”
Section: Barrier 2: Lack Of Diversity Among Practitionersmentioning
confidence: 99%